2000
DOI: 10.1364/ao.39.004911
|View full text |Cite
|
Sign up to set email alerts
|

Sealed-cell mercury resonance ionization imaging detector

Abstract: A sealed, compact mercury atomic-absorption resonance ionization imaging detector has been developed and evaluated. The sensitivity of the detector as well as its ability to form two-dimensional images has been demonstrated. Images of faint light (1000 photons) have been recorded by image summation. It is shown that one can obtain high-quality images with a spatial resolution of at least 130 mum by detecting the ionic component of the imaging signal. Distortion, more noise, and poorer spatial resolution were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The configuration and detailed principle of operation of the RIID are described elsewhere. [1][2][3][4] Briefly, the detector, consisting of a partially metal coated input window and a microchannel plate coupled with a P20 phosphor screen, was assembled in a six-way cross-vacuum chamber. The chamber was evacuated to a pressure of ϳ1 torr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration and detailed principle of operation of the RIID are described elsewhere. [1][2][3][4] Briefly, the detector, consisting of a partially metal coated input window and a microchannel plate coupled with a P20 phosphor screen, was assembled in a six-way cross-vacuum chamber. The chamber was evacuated to a pressure of ϳ1 torr.…”
Section: Methodsmentioning
confidence: 99%
“…The figure of merit of these detectors as well as their potential applications have been extensively discussed. 1 An RIID based on Hg vapor was first described by Matveev et al 2 and subsequently optimized by Pappas et al 3 Recently, another RIID using Cs as an active element was successfully demonstrated and its operational characteristics were evaluated. 4 The present note, as a continuation of the RIID development, describes a detector with two active elements (Cs and Hg), which exhibits dual-wavelength detection capability.…”
Section: Introductionmentioning
confidence: 99%
“…Several imaging detectors based on the uorescence or ionization of m ercury have been reported. [8][9][10][11][12][13] M atveev et al 10 have used a resonance uorescence imaging monochrom ator (RFIM ) to create two-dimensional images using two-step excitation in m ercury vapor. Finkelstein et al 8 and M iles et al 9 have demonstrated a one-step mercury imaging detector for rotational Raman imaging.…”
Section: Introductionmentioning
confidence: 99%